2006
DOI: 10.1091/mbc.e06-07-0619
|View full text |Cite
|
Sign up to set email alerts
|

A Phg2-Adrm1 Pathway Participates in the Nutrient-controlled Developmental Response inDictyostelium

Abstract: Dictyostelium amoebae grow as single cells but upon starvation they initiate multicellular development. Phg2 was characterized previously as a kinase controlling cellular adhesion and the organization of the actin cytoskeleton. Here we report that Phg2 also plays a role during the transition between growth and multicellular development, as evidenced by the fact that phg2 mutant cells can initiate development even in the presence of nutrients. Even at low cell density and in rich medium, phg2 mutant cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…Phosphoproteome analysis suggested that polyphosphate may have caused Adrm1 phosphorylation at residue T280 in three of the four trials, although polyphosphate did not significantly affect levels of Adrm1 (Table S1). To determine whether cells lacking Adrm1 have altered proteasome activity, we examined the proteasome activity levels of wild-type and adrm1 − cells (Cherix et al, 2006). Compared to wild-type cells, adrm1 − cells had abnormally low levels of proteasome activity ( Fig.…”
Section: Polyphosphate Induces Development In the Presence Of Nutrientsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phosphoproteome analysis suggested that polyphosphate may have caused Adrm1 phosphorylation at residue T280 in three of the four trials, although polyphosphate did not significantly affect levels of Adrm1 (Table S1). To determine whether cells lacking Adrm1 have altered proteasome activity, we examined the proteasome activity levels of wild-type and adrm1 − cells (Cherix et al, 2006). Compared to wild-type cells, adrm1 − cells had abnormally low levels of proteasome activity ( Fig.…”
Section: Polyphosphate Induces Development In the Presence Of Nutrientsmentioning
confidence: 99%
“…2A). Unlike wild-type cells, Dictyostelium cells lacking Adrm1 transition from vegetative growth to development while still in the presence of nutrients, suggesting a defect in the pre-starvation response and/or the GDT (Cherix et al, 2006). To determine whether the starvation-induced GDT is associated with a decrease in proteasome activity, the proteasome activity levels of starved cells was measured.…”
Section: Polyphosphate Induces Development In the Presence Of Nutrientsmentioning
confidence: 99%
See 3 more Smart Citations